Visualization of barriers and obstacles to molecular diffusion in live cells by spatial pair-cross-correlation in two dimensions - Malacrida, Leonel (Biomed Opt Express, 2017)
Despite recent advances in optical super-resolution, we lack a method that can visualize the path followed by diffusing molecules in the cytoplasm or in the nucleus of cells. Fluorescence correlation spectroscopy (FCS) provides molecular dynamics at the single molecule level by averaging the behavior of many molecules over time at a single spot, thus achieving very good statistics but at only one point in the cell. Earlier image-based methods including raster-scan and spatiotemporal image correlation need spatial averaging over relatively large areas, thus compromising spatial resolution. Here, we use spatial pair-cross-correlation in two dimensions (2D-pCF) to obtain relatively high resolution images of molecular diffusion dynamics and transport in live cells. The 2D-pCF method measures the time for a particle to go from one location to another by cross-correlating the intensity fluctuations at specific points in an image. Hence, a visual map of the average path followed by molecules is created.